DASAR PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA PIDANA PENCABULAN TERHADAP ANAK (ANALISA PUTUSAN PERKARA NOMOR : 150/Pid.Sus/2019/PN.BYL) - Sarjono Sarjono; Burham Pranawa; Tegar Harbriyana Putra (Fakultas Hukum Universitas Boyolali, 2020)
Fornication is a “criminal offense against decency which develop from time to time and requires special handling. The crime of sexual abuse against children need serious attentions from all circle, especially the active role of law enforcers.” Imposing a crime against the perpetrator of a criminal act of sexual immorality cannot be separated from the role of judges, prosecutors and the police as law enforcement officers in order to achieve peace in the life of the community. The purpose of this research is to know the judges 'considerations in deciding criminal cases against children, knowing the judges' “settlement of witnesses who are less than 15 years old in the District Court in deciding criminal cases for perpetrator who have commited obscene act against children,” knowing the obstacles faced by judges in deciding criminal cases of obscenity Against Children in Boyolali District Court Decision Number: 150 / Pid.Sus / 2019 / PN.BYL. The research conducted is a descriptive legal research with an yurisdis empirical approach which take primary data by conducting interview and secondarry data by procesing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results of Judges' considerations in deciding criminal cases of child sexual abuse in the Boyolali District Court Decision Number: 150 / Pid.Sus / 2019 / PN.BYL, “that the elements of Article 82 paragraph (1), (2) Law of the Republic of Indonesia Number 17 2016 concern Stipulation of Perpu Number 1 of 2016 concerning the Second Amendment to Law of the Republic of Indonesia Number 23 of 2002 concern Child Protection as amended and supplemented by Law Number 35 of 2014 concerning Amendment to Law Number 23 of 2002 concern Child Protection has been fulfilled, and the Defendant is legally and convincingly proven to have committed the criminal act as charged in the Single Indictment.” According to Lawrence Meir Friedman's theory, “this is called a substantial system that determines whether or not the law is implemented. Substance also means products produced by people who are in the legal system which include the decisions they issue, the new rules they draft.” ABSTRAK Pencabulan termasuk salah satu tindak pidana terhadap kesusilaan yang semakin ada perkembangan dari waktu ke waktu dan memerlukan penanganan secara khusus. Tindak pidana pencabulan terhadap anak perlu memperoleh perhatian serius dari berbagai kalangan, utamanya peran aktif pihak penegak hukum. Pidana dijatuhkan untuk pelaku tindak pidana pencabulan tentu saja tidak lepas dari peranan jaksa, hakim, dan pihak kepolisian sebagai aparat penegak hukum untuk meraih ketentraman hidup masyarakat. Tujuan penelitian ini Untuk Mengetahui Pertimbangan Hakim Dalam Memutuskan Perkara Pidana Pecabulan Terhadap Anak, Mengetahui Penyelesaian hakim Terhadap Saksi yang berumur kurang 15 tahun di PN dalam memutuskan perkara pidana pelaku yang melakukan perbuatan cabul terhadap anak, Mengetahui kendala yang dijumpai oleh Hakim Dalam Memutuskan Perkara Pidana Pecabulan Terhadap Anak dalam Putusan PN Boyolali Nomor: 150/Pid.Sus/2019/PN.BYL. Penelitian yang dilakukan merupakan penelitian hukum deskriptif melalui pendekatan yurisdis empiris yang didapatkan data primer melalui wawancara dan data sekunder melalui pengolahan data dari bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Sesuai hasil penelitian Pertimbangan Hakim untuk memutuskan perkara pidana Pencabulan Terhadap Anak dalam Putusan PN Boyolali No.: 150/Pid.Sus/2019/PN.BYL, “unsur Pasal 82 ayat (1), (2) Undang-undang Republik Indonesia No. 17 tahun 2016 Tentang Penetapan Perpu Tahun 2016 No. 1 tentang Perubahan Kedua atas Undang-undang Republik Indonesia Nomor 23 Tahun 2002 tentang Perlindungan Anak sebagaimana telah diubah dan ditambah dengan Undang-undang Nomor 35 tahun 2014 tentang Perubahan Undang-undang Nomor 23 Tahun 2002 tentang Perlindungan Anak telah terpenuhi, dan Terdakwa dinyatakan terbukti dengan sah dan meyakinkan melakukan tindak pidana sebagaimana didakwakan dalam Dakwaan Tunggal.” Teori Lawrence Meir Friedman menyatakan “hal ini disebut sebagai sistem Subtansial yang menentukan bisa atau tidaknya hukum itu dilaksanakan. Subtansi juga berarti produk yang dihasilkan oleh orang yang berada dalam sistem hukum yang mencakup keputusan yang mereka keluarkan, aturan baru yang mereka susun.”